Coastal Biodiversity Of Tidung & Rambut Islands: Mangrove And Coral Reef Conservation Program - Basuki Wicaksono; Tiaraningrum; Fauziah Ilmi; Fauzan Cholifatullah; Silvia Hasan; Nonon Saribanon (Journal of Tropical Biodiversity, 2022)
Kepulauan Seribu have different characteristics ecosystem to conduct in increasing of tourism and fishery activities. Thus, there is a need for efforts to restore damaged habitats as a result of tourism activities. Restoration of mangroves and coral reefs needs to be carried out to maintain existing natural resources. Based on this background, the research aims to determine the survival rate, composition, diversity and evenness of mangrove and coral reefs in Research area. The research was conducted in three location (Tidung Island, Rambut Island, and PT.Pertamina Plumpang) held along in May untill October 2022. The method for plant vegetation and mangrove based by quadran and non-transect sampling as the 10% representation of area, meanwhile in fauna method based by VES (Visual Encounter Survey), also Coral based by LIT (Line Intercept Transect). The diversity index value of flora is 3,176 in PT.Pertamina Plumpang, classified as high. The evenness index is 0.808; relatively high. The estimated value of biomass and carbon stock of plant tree in PT.Pertamina Plumpang is 57314,01 ton/Ha. The persentage existence of Mangrove in Tidung Island is 33%; Rambut Island 37%. The survival rate persentage of coral in Tidung Island is 97% existence, despite 3% in mortality. The composition of avifauna in PT.Pertamina Plumpang is 12 species include in 10 family. The avifauna diversity index value is 1.88, which indicates in medium category. The evenness index value of avifauna is 0.75, which is a high value. The composition of herpetofauna include in 2 species, besides in insecta found 6 species.